Simulation of the crack width in reinforced concrete beams based on concrete fracture. (October 2022) - Cervenka, Vladimir; Rimkus, Arvydas; Gribniak, Viktor; Cervenka, Jan
Highlights: Nonlinear simulation predicts crack width and pattern in reinforced concrete beams. Importance of fracture mechanics based models for accurate predictions. Assessment of model uncertainty for crack width prediction by nonlinear simulation. Experimental assessment of the crack width in reinforced concrete beams. Effect of concrete fracture energy, shrinkage and reinforcement arrangement on the crack width. Abstract: The concrete cracking is simulated by the finite element method combined with the constitutive model based on the nonlinear fracture mechanics. The model uncertainties for mean and maximum crack widths are found by comparing the simulated crack widths with data obtained by laboratory testing of 18 reinforced concrete beams. The reinforcement arrangement, dimensional simplification, and numerical discretisation effects on the model uncertainty are investigated. Two reinforcement types, i.e. steel and glass fibre-reinforced polymer bars, are considered. The shrinkage effect on the cracking predictions is included. The fracture energy parameter according to fib Model Code 2010 is used in the simulations. The numerical model offers an adequate prediction of crack widths for the beams with a single layer reinforcement and exhibits less accuracy for the multilayer bar arrangement. The presented numerical model represents an advanced tool for the crack width assessment in the design of reinforced concrete structures in serviceability limit states.